Post a New Question

algebra 11

posted by .

(K+1)x+2y=6; M=k-2

  • algebra 11 -

    Apparently you mean that M is the slope. Most folks use lower-case letters.

    In any case, we have

    2y = -(k+1)x + 6
    y = -(k+1)/2 x + 3
    The slope is -(k+1)/2

    -(k+1)/2 = k-2
    -(k+1) = 2k - 2
    -k-1 = 2k-2
    3k = 1
    k = 1/3

  • algebra 11 -

    oops
    -(k+1) = 2k - 4
    -k-1 = 2k-4
    3k=3
    k=1

  • algebra 11 -

    Steve, You made another mistake in that second edit.

    Once you reach -k-1=2k-4.

    You need to subtract 2k from the right side.
    That gets you -3k-1=-4.

    You add 1 to get rid of that negative one which gets -3k=-3. Solve for k=1

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question